Binding Specificity of Native Odorant-Binding Protein Isoforms Is Driven by Phosphorylation and O-N-Acetylglucosaminylation in the Pig Sus scrofa - Nagnan-Le Meillour, Patricia; Joly, Alexandre; Le Danvic, Chrystelle; Marie, Arul; Zirah, Séverine; Cornard, Jean-Paul (Frontiers in Endocrinology, 2019)
Odorant-binding proteins (OBP) are secreted in the nasal mucus at the vicinity of olfactory receptors (ORs). They act, at least, as an interface between hydrophobic and volatile odorant molecules and the hydrophilic medium bathing the ORs. They have also been hypothesized to be part of the molecular coding of odors and pheromones, by forming specific complexes with odorant molecules that could ultimately stimulate ORs to trigger the olfactory transduction cascade. In a previous work, we have evidenced that pig olfactory secretome was composed of numerous olfactory binding protein isoforms, generated by O-GlcNAcylation and phosphorylation. In addition, we have shown that recombinant OBP (stricto sensu) produced in yeast is a mixture of isoforms that differ in their phosphorylation pattern, which in turn determines binding specificity. Taking advantage of the high amount of OBP secreted by a single animal, we performed a similar study, under exactly the same experimental conditions, on native isoforms isolated from pig, Sus scrofa, nasal tissue. Four fractions were obtained by using strong anion exchange HPLC. Mapping of phosphorylation and O-GlcNAcylation sites by CID-nanoLC-MS/MS allowed unambiguous localization of phosphosites at S13 and T122 and HexNAc sites at S13 and S19. T112 or T115 could also be phosphorylated. BEMAD analysis suggested extra phosphosites located at S23, S24, S41, S49, S57, S67, and T71. Due to the very low stoichiometry of GlcNAc-peptides and phosphopeptides, these sites were identified on total mixture of OBP isoforms instead of HPLC-purified OBP isoforms. Nevertheless, binding properties of native OBP isoforms to specific ligands in S. scrofa were monitored by fluorescence spectroscopy. Recombinant phosphorylated OBP-Pichia isoforms bind steroids and fatty acids with slight differences. Native isoforms, that are phosphorylated but also O-GlcNAcylated show radically different binding affinities for the same compounds, which strongly suggests that O-GlcNAcylation increases the binding specificity of OBP isoforms. These findings extend the role of O-GlcNAc in regulating the function of proteins involved in many metabolism homeostasis, including extracellular signaling in olfaction. Data are available via ProteomeXChange with identifier PXD011371.